Effects of Caffeine on Brown Adipose Tissue Thermogenesis and Metabolic Homeostasis: A Review - Van Schaik, Lachlan; Kettle, Christine; Green, Rodney; Irving, Helen R.; Rathner, Joseph A. (Frontiers in Neuroscience, 2021)
The impact of brown adipose tissue (BAT) metabolism on understanding energy balance in humans is a relatively new and exciting field of research. The pathogenesis of obesity can be largely explained by an imbalance between caloric intake and energy expenditure, but the underlying mechanisms are far more complex. Traditional non-selective sympathetic activators have been used to artificially elevate energy utilization, or suppress appetite, however undesirable side effects are apparent with the use of these pharmacological interventions. Understanding the role of BAT, in relation to human energy homeostasis has the potential to dramatically offset the energy imbalance associated with obesity. This review discusses paradoxical effects of caffeine on peripheral adenosine receptors and the possible role of adenosine in increasing metabolism is highlighted, with consideration to the potential of central rather than peripheral mechanisms for caffeine mediated BAT thermogenesis and energy expenditure. Research on the complex physiology of adipose tissue, the embryonic lineage and function of the different types of adipocytes is summarized. In addition, the effect of BAT on overall human metabolism and the extent of the associated increase in energy expenditure are discussed. The controversy surrounding the primary β-adrenoceptor involved in human BAT activation is examined, and suggestions as to the lack of translational findings from animal to human physiology and human in vitro to in vivo models are provided. This review compares and distinguishes human and rodent BAT effects, thus developing an understanding of human BAT thermogenesis to aid lifestyle interventions targeting obesity and metabolic syndrome. The focus of this review is on the effect of BAT thermogenesis on overall metabolism, and the potential therapeutic effects of caffeine in increasing metabolism via its effects on BAT.